(untitled) (Veterinary Science, 2017)
This article shows the need to maintain rigueur in applying the scientific method through the analysis of two publications on the topic of mycobacterium sporulation. It also shows the importance of the evaluators and editors of scientific magazines real work to avoid the fraud and confusion in establishing a new paradigm.